A systematic review of instruments for assessing parent satisfaction with family-centred care in neonatal intensive care units - Dall'Oglio, I.; Mascolo, R.; Gawronski, O.; Tiozzo, E.; Portanova, A.; Ragni, A.; Alvaro, R.; Rocco, G.; Latour, Jos (Wiley-Blackwell Publishing Ltd., 2018)
This systematic review synthesised and described instruments measuring parent satisfaction with the increasing standard practice of family-centred care (FCC) in neonatal intensive care units. We evaluated 11 studies published from January 2006 to March 2016: two studies validated a parent satisfaction questionnaire, and nine developed or modified previous questionnaires to use as outcome measures in their local settings. Most instruments were not tested on reliability and validity. Conclusion: Only two validated instruments included all six of the FCC principles and could assess parent satisfaction with FCC in neonatal intensive care units and be considered as outcome indicators for further research.